Exploring the complexities of 1C metabolism: implications in aging and neurodegenerative diseases - Bou Ghanem, Ayman; Hussayni, Yaman; Kadbey, Raghid; Ratel, Yara; Yehya, Shereen; Khouzami, Lara; Ghadieh, Hilda E.; Kanaan, Amjad; Azar, Sami; Harb, Frederic (Frontiers in Aging Neuroscience, 2024)
The intricate interplay of one-carbon metabolism (OCM) with various cellular processes has garnered substantial attention due to its fundamental implications in several biological processes. OCM serves as a pivotal hub for methyl group donation in vital biochemical reactions, influencing DNA methylation, protein synthesis, and redox balance. In the context of aging, OCM dysregulation can contribute to epigenetic modifications and aberrant redox states, accentuating cellular senescence and age-associated pathologies. Furthermore, OCM’s intricate involvement in cancer progression is evident through its capacity to provide essential one-carbon units crucial for nucleotide synthesis and DNA methylation, thereby fueling uncontrolled cell proliferation and tumor development. In neurodegenerative disorders like Alzheimer’s and Parkinson’s, perturbations in OCM pathways are implicated in the dysregulation of neurotransmitter synthesis and mitochondrial dysfunction, contributing to disease pathophysiology. This review underscores the profound impact of OCM in diverse disease contexts, reinforcing the need for a comprehensive understanding of its molecular complexities to pave the way for targeted therapeutic interventions across inflammation, aging and neurodegenerative disorders.